2015
DOI: 10.1007/s40626-015-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soluble amino acid composition during Canavalia ensiformis development: responses to nitrogen deficiency

Abstract: A limited number of studies focusing nitrogen metabolism have been carried out with plants from Cerrado, the second largest biome of Brazil. Canavalia ensiformes is a legume native from Cerrado and is considered an important forage crop that contributes to soil nitrogen (N) improvement. There are few studies related to amino acid metabolism and growth capacity under nitrogen deficiency for this plant species. Therefore, the objective of this work was to study the profile of soluble amino acids during the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The application of nitrate to lentil (Lens culinaris Medic. ), faba bean (Vicia faba L.), pea (Pisum sativum L.) and Canavalia ensiformes significantly increased the Asn content in the roots [11,12]. Ohyama and Kumazawa [13] found that the level of 15 N in Asn present in the roots was considerably greater compared to the other amino acids after the soybean roots were exposed to 15 NO 3 − for a duration of eight hours.…”
Section: Introductionmentioning
confidence: 99%
“…The application of nitrate to lentil (Lens culinaris Medic. ), faba bean (Vicia faba L.), pea (Pisum sativum L.) and Canavalia ensiformes significantly increased the Asn content in the roots [11,12]. Ohyama and Kumazawa [13] found that the level of 15 N in Asn present in the roots was considerably greater compared to the other amino acids after the soybean roots were exposed to 15 NO 3 − for a duration of eight hours.…”
Section: Introductionmentioning
confidence: 99%
“…Asparagine and glutamine are linked to the metabolism of nitrogen in plants, wherein the first transports organic nitrogen, due to its structural characteristics, such as low C:N ratio, high solubility, stability and mobility in physiological fluids and, the second one assimilates the carried forms of nitrogen (ammonium and nitrate), controlling this nutrient in the plant organism, in order to avoid it to cause phytotoxic effects on plants . On the other hand, cysteine and proline are related to plant defense metabolism because the majority of the isolated antimicrobial peptides present six to eight cysteines linked by disulfide bridges , and proline, which is expressed under environmental stress conditions, adjusts subcellular structures, such as membranes and proteins, neutralizes free radicals and reduces the redox potential under conditions of stress .…”
Section: Introductionmentioning
confidence: 99%